Modification agility test in tarung derajat sport - Surya, Amanda Dara; Komarudin, Komarudin; Yusup, Ucup; Novian, Geraldi (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2024)
This study aims to determine the value of validity and reliability of agility test modifications in sport Tarung Derajat. Therefore, researchers made one of the new agility test modification models that are suitable and specific based on the characteristics of the Tarung Derajat sport which will later be tested for validity and reliability under the name 4-Direction Agility Fighting (4-DAF) modification. The research method used is the research and development method (Research and Development). The population in this study was 20 athletes from Pengcab Tarung Derajat in Kuningan regency consisting of 12 male athletes and 8 female athletes. Sampling using saturated sampling technique. The data was collected using modified instruments named 4-Direction Agility Fighting (4-DAF) and Right Boomerang Run as comparison instruments. Analysis of validity test data using pearson correlation and reliability test using Cronbach alpha test with the help of data processing using SPSS Statistics version 21. The results showed a large validity value of 4-Direction Agility Fighting (4-DAF) of 0.838 and a large reliability value of 0.987. The conclusion of this study shows that 4-Direction Agility Fighting (4-DAF) has good validity and reliability values and can be used to measure the agility level of Tarung Derajat athletes .